PENINGKATAN KINERJA GURU MELALUI KEPEMIMPINAN KEPALA SEKOLAH, PELATIHAN, DAN KOMPETENSI GURU PADA SEKOLAH KHUSUS DI KOTA TANGERANG SELATAN - Aam Marhamah Marhamah; Yulita Pujilestari Pujilestari; Estiningsih Trihandayani Trihandayani (STKIP Subang, 2026)
This study examines how the effectiveness of school principals’ leadership, the continuity of training programs, and the strengthening of teachers’ competencies simultaneously serve as strategic solutions to overcome existing challenges and improve the quality of inclusive education services. The research employed a quantitative method with an associative approach. The research population consisted of 163 teachers, with a sample of 116 respondents selected using the Proportional Random Sampling technique. Data were collected through Likert-scale questionnaires and analyzed using multiple linear regression with the assistance of SPSS software. The results indicate that: (1) school principals’ leadership has a positive and significant effect on teacher performance, with a very strong relationship (r = 0.948) and a contribution of 89.9%; (2) training has a positive and significant effect on teacher performance, with a very strong relationship (r = 0.876) and a contribution of 76.7%; (3) teacher competence has a positive and significant effect on teacher performance, with a very strong relationship (r = 0.849) and a contribution of 72%; and (4) simultaneously, school principals’ leadership, training, and teacher competence have a significant effect with a very strong relationship (r = 0.961) and a coefficient of determination of 0.924. This indicates that 92.4% of the variation in teacher performance is explained by the synergy of school principals’ leadership, training, and teacher competence, while the remaining 7.6% is influenced by other factors outside this research model.